A Decision Framework for Selecting Highly Sustainable Packaging Circular Model in Mass-Customized Packaging Industry - Ravishankar Rajendran; Sudhakarapandian Ranjitharamasamy (Applied Sciences)
The selection of a sustainable packaging circular model approach entails numerous obstacles under rapidly developing circumstances, such as environmental factors, market competition, and advancing technology, impacting decision-making processes. We have considered Z-number-based decision-making methods as an alternative to the conventional method. This study presents a selection of circular sustainable packaging models, considering significant challenges from five primary objectives: economic, environmental, social responsibility, sustainability, and time-based, with three circular models: biodegradable, compostable, and recycling. The ZF-DEMATEL-TOPSIS method is used in an integrated manner to address the packaging circular model selection problem. The study results indicate that the mass-customized recyclable packaging circular model is the most highly sustainable among the three models. At the same time, the most significant challenges are production cost, energy efficiency, and makespan. The proposed method was validated using the sensitivity analysis with an 90% consistency ratio. We conducted this study to aid in analyzing and developing a highly sustainable mass-customized circular packaging model.